Conducta obstétrica ante amenaza de parto pretérmino, en gestante de 21 años más consumo de drogas. - Morales Parraga, María Ivonne (2021)
Currently and worldwide it is considered that one of the problems that harm society is the consumption or intake of toxic substances (drugs) which affects regardless of gender, sex, socioeconomic status, ethnicity and more, being part of this group of drug users, pregnant women. Complications that occur due to drug use by pregnant women affect both the mother and the fetus, since when they stop using substances due to the onset of labor, both suffer similar symptoms resulting from withdrawal syndrome. The consumption of drugs by pregnant women causes an increase in neonatal morbidity, as well as the possible development of pathologies in the child (physical and cognitive) and in some cases the death of the child.